2005
DOI: 10.14507/epaa.v13n16.2005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of degree field on the earnings of male and female college graduates

Abstract: Since the gender demographics across majors have dramatically changed over the last few decades, a re-examination of the relationship between gender, undergraduate major selection, and compensation levels once in the workforce is important. This article will focus on how the salaries of college graduates have changed over the last decade. The analyses will explore the extent to which undergraduate major selection contributes to any male-female salary gap. A comparison of regression models for 1993 and 2001 des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Of the 6645 bachelor's degrees awarded in Education, females accounted for 5044 (75.9%, but 4.9% of total) and males accounted for 1601 (24.1%, but 3% of total). In science, mathematics and engineering fields males continue to earn more degrees in mathematics and engineering (Freeman et al, 2005; also see Ma, 2009), which is also observed in Table 2.…”
Section: Degree Attainment In Science and Engineeringsupporting
confidence: 62%
“…Of the 6645 bachelor's degrees awarded in Education, females accounted for 5044 (75.9%, but 4.9% of total) and males accounted for 1601 (24.1%, but 3% of total). In science, mathematics and engineering fields males continue to earn more degrees in mathematics and engineering (Freeman et al, 2005; also see Ma, 2009), which is also observed in Table 2.…”
Section: Degree Attainment In Science and Engineeringsupporting
confidence: 62%